The Role of Families in Preventing Uric Acid Relapse in the Elderly in SilagaVillage, Siniu District, Parigi Moutong Regency - Niswa Salamung; Noviany Banne Rasiman; Maftuha Maftuha; Ni Ketut Elmiyanti; Freny Ravika Mbaloto (Universitas Bondowoso, 2021)
Introduction: Gout or commonly called gout arthritis is a disease that arises suddenly, repeatedly and is very painful, which generally occurs in the big toe or other joints. The elderly said they did not get information and support from their families about how to prevent gout recurrence. The purpose of this study was to determine the role of the family in the prevention of gout recurrence in the elderly in Silanga Village, Siniu District, ParigiMoutong Regency. Method: The type of research used is descriptive research, the population in this study is the elderly who suffer from gout in Silanga Village, Siniu District, ParigiMoutong Regency, a total of 39 people. The sample in this study was the entire population as a sample, amounting to 39 people. The sampling method is non-probability sampling with a total sampling approach model. Result: It shows that of 39 respondents stated that most of the family roles are sufficient (53.8%), good family roles (23.1%) and less family roles (23.1%). It is hoped that families will give more roles to gout sufferers, namely in the form of a role as a motivator, a role as an educator, and a role as a family nurse. Suggestions for health workers to be more active in providing information about gout, causative factors, and ways to prevent gout recurrence and always involve families to assist the elderly. Conclusion: It is hoped that the family will increase the role given to the elderly in preventing the recurrence of gout in terms of the role as a motivator.